Pengaruh Work From Home Terhadap Kinerja Karyawan Di Batam - Kelvyn Kelvyn; Ellwan Edy Wei; Christopher Khomali; Hosse Fernando; Veri Hartanto (Sains: Jurnal Manajemen dan Bisnis, 2021)
This study aims to obtain empirical evidence about the effect of work from home on employees job performance taken from the respondents. This analysis using independent variables WFH (work from home), work environment, job satisfaction, and work motivation. The dependent variable is job performance. Samples in this study were the college students who ever or currently working with working from home system in Batam city. This study used a sample method of Stratified Disproportionate Random Sampling with total sample of 150 respondents. This is a quantitative study that distributes data and questionnaires. Data analysis in this study was analyzed using regression using SPSS software. The three supporting factors, work environment, job satisfaction, and job motivation affect the job performance in Batam city. This study proves that work motivation and job satisfaction have positive influence on job performance. From the result, we hope this research can be useful as knowledge and consideration for government or company whether need to continue the implementation of work from home system or not.